2020
DOI: 10.3892/etm.2020.9555
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nutritional index predicts acute kidney injury and mortality of patients in the coronary care unit

Abstract: The current study aimed to investigate whether prognostic nutritional index (PNI) is an independent predictor of acute kidney injury (AKI) and mortality of patients in the coronary care unit (CCU). In the present two-stage observational study of patients in the CCU, 6,444 patients from the Medical Information Mart for Intensive Care (MIMIC) III database were first enrolled (test cohort), after which 412 patients from Zhongnan Hospital of Wuhan University were recruited in the validation cohort. AKI was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…Malnutrition is common in patients with AKI and affects the occurrence and development of AKI independently of nonnutritional factors, increasing hospital death, complications, and medical costs [16][17][18]. In an observational study which recruited 6,444 patients from the Medical Information Mart for Intensive Care (MIMIC) III database and 412 patients from Zhongnan Hospital of Wuhan University conducted by Hu et al, the results demonstrated that PNI value was an independent predictor of AKI in patients within the coronary-care unit [8]. ere are some similarities between this study and ours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malnutrition is common in patients with AKI and affects the occurrence and development of AKI independently of nonnutritional factors, increasing hospital death, complications, and medical costs [16][17][18]. In an observational study which recruited 6,444 patients from the Medical Information Mart for Intensive Care (MIMIC) III database and 412 patients from Zhongnan Hospital of Wuhan University conducted by Hu et al, the results demonstrated that PNI value was an independent predictor of AKI in patients within the coronary-care unit [8]. ere are some similarities between this study and ours.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that malnutrition was common in patients with coronary artery disease (CAD) [5], and malnutrition was closely related to the occurrence of acute kidney injury (AKI) in hospitalized patients [6][7][8]. e prognostic nutritional index (PNI) is a screening tool for the nutritional status and has been described as a simple and objective indicator [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, more attention has been paid to the impact of nutritional and immune status on the prognosis of various cancers. PNI has been reported as a simple and objective indicator of patient Nutrients 2021, 13, 1604 2 of 13 survival and complications in acute and chronic diseases, such as AKI, heart failure, and various cancers [10][11][12][13][14]. Moreover, PNI was reported to be associated with postoperative complications and surgical prognosis in patients with colorectal cancer surgery [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic nutritional index (PNI), a biological marker, which can be determined through the serum albumin level and total lymphocyte count in peripheral blood, reflects a patient’s nutritional and inflammatory status [ 14 ]. The PNI was reportedly associated with survival or complications in various diseases, including cancer [ 15 , 16 , 17 , 18 ]. Recent studies have also indicated that the PNI is an effective predictor of prognosis in patients with HCC after hepatectomy [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%